2000
DOI: 10.1007/s001270050232
|View full text |Cite
|
Sign up to set email alerts
|

Generality of support sources and psychometric properties of a scale of perceived social support in Turkey

Abstract: The generality of support sources, with some differing definitions, was supported. The psychometric properties of the MSPSS were adequate for it to be used in Turkey. However, social support may be especially relevant for groups with psychological/medical problems, and support from close people (particularly the family) may be especially predictive of health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 18 publications
4
33
1
4
Order By: Relevance
“…In Colombia, there is no evidence regarding the psychometric properties of this scale in the adolescent population. The internal consistency coefficient, Cronbach's alpha, values for the 12 items of the MSPSS have demonstrated excellent internal reliability from previous studies that have used a variety of subject's samples: α = .91 (Dahlem et al, 1991); α = .87 ± .94 (Stanley et al, 1998); α = .93 (Canty-Mitchell & Zimet, 2000); α = .89 (Chou, 2000); α = .80 ± .95 (Eker et al, 2000); α = .86 (Arechabala & Miranda, 2002); α = .91 ± .95 (Pedersen et al, 2009); α = .89 (Ng et al, 2010); α = .84 (Ortiz & Baeza, 2011); α = .90 (Tonsing et al, 2012); α = .80 (Pinto et al, 2014), and α = .88 (Mosqueda et al, 2015). The factor analyses of the studies mentioned above confirmed the three subscale structures of the MSPSS: family, friends, and significant other to account between 79.3% and 83.9% of the variance.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…In Colombia, there is no evidence regarding the psychometric properties of this scale in the adolescent population. The internal consistency coefficient, Cronbach's alpha, values for the 12 items of the MSPSS have demonstrated excellent internal reliability from previous studies that have used a variety of subject's samples: α = .91 (Dahlem et al, 1991); α = .87 ± .94 (Stanley et al, 1998); α = .93 (Canty-Mitchell & Zimet, 2000); α = .89 (Chou, 2000); α = .80 ± .95 (Eker et al, 2000); α = .86 (Arechabala & Miranda, 2002); α = .91 ± .95 (Pedersen et al, 2009); α = .89 (Ng et al, 2010); α = .84 (Ortiz & Baeza, 2011); α = .90 (Tonsing et al, 2012); α = .80 (Pinto et al, 2014), and α = .88 (Mosqueda et al, 2015). The factor analyses of the studies mentioned above confirmed the three subscale structures of the MSPSS: family, friends, and significant other to account between 79.3% and 83.9% of the variance.…”
mentioning
confidence: 73%
“…The MSPSS is brief, of easy application and use, which is favorable when the subject has little time or when several measures must be administered. Furthermore, the MSPSS has demonstrated psychometric validity in several studies conducted in different populations of adolescents and adults worldwide (Canty-Mitchell & Zimet, 2000;Cecil, Stanley, Carrion, & Swann, 1995;Chou, 2000;Kee-Lee, 2000;Dahlem, Zimet, & Walker, 1991;Eker, Arkar, & Yaldiz, 2000;Kazarian & MacCabe, 1991;Stanley, Beck, & Zebb, 1998;Zimet et al, 1988;Zimet, Powell, Farley, Werkman, & Berkoff, 1990), and validations continue to be performed with satisfactory results in terms of internal consistency (Arechabala & Miranda, 2002;Chou, 2000;Mosqueda, Mendoza, Jofré, & Barriga, 2015;Ng, Amer Siddiq, Aida, Zainal, & Koh 2010;Ortiz & Baeza, 2011;Pedersen, Spinder, Erdman, & Denollet, 2009;Pinto, Lara, Espinoza, & Montoya, 2014;Tonsing, Zimet, & Tse, 2012). On the other hand, exploratory factor analyses have shown that a 3-factor structure is suitable for the MSPSS in adolescent and adult populations with ethnic and socioeconomic diversity.…”
mentioning
confidence: 99%
“…This instrument allows the assessment of the subject’s perception of the adequacy of support from family, friends and significant others. Many studies have provided evidence of reliability and validity for the questionnaire [19, 20, 21, 22]. The MSPSS gives three subscale scores (family support, friends support, others support), which can be added to give a Total Social Support score.…”
Section: Methodsmentioning
confidence: 99%
“…Even so, a second study was conducted to make the usage of the scale culturally more appropriate by strengthening the construct validity of "significant other" subscale (Eker et al, 2000). In the second study, Cronbach's alpha coefficients for the total scale score were reported as ranging from .83 to .91 and that alpha for subscales ranged from .80 to .95, indicating high internal consistency for both the three subscales and the total scale.…”
Section: Journal Of Divorce and Remarriagementioning
confidence: 99%